Upaya guru dalam mengatasi penggunaan bahasa daerah pada mata pelajaran bahasa indonesia di sekola MIS Jadil Maad Aloindonu - Lutfia Tika Dewi Ahmad; Ismail Tamal Biat; Mahmud Abdullah Noho (Jurnal Edukasi, 2026)
Teachers' efforts in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu School. The purpose of this study was to determine the efforts of teachers in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu. Teachers' efforts in overcoming the use of regional languages ​​in the Indonesian Language subject for grade III at MIS Zadil Maad Aloindonu and to find out what inhibiting factors the school faced in overcoming the use of regional languages ​​in grade III at MIS Zadil Maad Aloindonu. Using a descriptive qualitative method. The subjects of this study were the principal, Indonesian Language teachers and students. Data collection techniques used were observation, interviews, and documentation with analysis techniques, namely data reduction, data display. The verbal rules made by the principal of MIS Zadil Maad Aloindonu reprimand students and teachers if they always use Indonesian at school or in learning, the principal also began to implement the use of Indonesian in the school environment, especially in learning and giving authority to each teacher and each homeroom teacher to make rules and punishments for students who use regional languages ​​too much at school or in learning ". The efforts of Indonesian language teachers are in the form of advising students, but the most prominent punishment is paying a fine because it can be seen from the fine that students feel they have lost money and try to use Indonesian. Inhibiting factors for the use of Indonesian in Indonesian language subjects. internal and external factors, where these internal factors come from within students that affect the intellectual capacity and interests and desires of the students themselves. While external factors are factors from the environment such as family and playmates.